Effect of service quality and company image on customer satisfaction mediated by price at CV. Rizqy Abadi Utama Jakarta - Alfiarini, Isni Ambar; Chandra, Rama (Indonesian Journal of Business, Accounting and Management, 2023)
This research examines the effects of service quality, price, and corporate image on customer satisfaction. It also aims to explore the indirect impact of service quality on customer satisfaction through price and the influence of corporate image on customer satisfaction via price. This study employs an associative research strategy. The population includes clients of CV. Rizqy Abadi Utama, with a sample size of 68 respondents who have used the company's distribution and licensing services. A purposive sampling technique was used, and data was collected through questionnaires, yielding primary data. The analysis was conducted using path analysis with the Partial Least Squares (PLS) method, explicitly utilizing WarpPLS 6.0 software. The study's findings conclude that service quality, price, and corporate image all positively influence customer satisfaction. However, regarding mediating effects, the study found that price does not mediate the relationship between service quality and customer satisfaction, nor does it fully mediate the relationship between corporate image and customer satisfaction. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.